YOUTH IDENTITY DEVELOPMENT ON THE BASIS OF TRADITIONAL KAZAKH FOLK MUSIC. - Bizhanova, Kenzhegul; Arinova, Bakyt; Akbayeva, Gulshat; Massimbayeva, Aiym (Folklore (14060957), 2024)
This study strived to determine the most popular music genre among young Kazakhs in the context of personal, social, and national identity development, specify the relationship between musical preferences and personality type, and disclose the level of influence of traditional Kazakh folk music on the identity of the Kazakh youth. The authors conducted a survey and a test by taking advantage of such research methods as sociological survey, statistical analysis, social phenomena cognition (assessment, analogy tracking, comparison), psychological and typological concepts of Jung, as well as Abulkhanova-Slavskaya's methodology for revealing personality traits. As a result of the investigation, hip-hop and rap were identified as the most popular music genres among the respondents (42.2%). Analysis of the data obtained in accordance with Abulhanova-Slavskaya's personality typology revealed that 89% of the respondents preferring blues/jazz, classical music, and folk music demonstrated personality traits corresponding to the reflexive personality type; 91% of punk/rock and heavy metal fans showed conformity to the contemplative personality type; 87.5% of pop-music lovers were attributed the harmonious personality type; 93.5% of hip-hop and rap music fans - the productive personality type; 84% of traditional music fans - the performing type; and 96% of fans of pop with folk tunes - the functional type. It was also uncovered that 89% of the respondents who preferred traditional music belonged to the sensitive personality type characterized by impressionability, openness, empathy, alertness, firmness, conscientiousness, and, at the same time, inferiority complexes, and a tendency to psychogenic depressions and phobias.